FAMILY ENVIRONMENT: THE ADAPTATION OF IDEAL FORM OF FAMILY ENVIRONMENT SCALE IN THE CULTURAL ENVIRONMENT OF LATVIA - Dombrovskis, Aivis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The tool for research the family environment, Family Environment Scale (FES) which is created by Moos and Moos in Latvia wasn’t adopted, that why is important to adopt this tool in environment of Latvia, because this will be chance for specialists to use good and multidimensional tool for research of family environment.The main goal of this article is to show the results of FES - R scale adaptation, this is why author in this article shows Family Environment Scale’s (Moos & Moos, 2009) Real form of scale adaptation in the environment of Latvia, the way of adaptation and comparative data for adapted and original version. FES - R had been adopted by using linguistic adaptation and statistical analysis for getting the general psychometric data which are necessary for process of the test adaptation and providing of validity for adaptation version of the test. At the result of process of adaptation with some insignificant changes in items of subscales of FES – R form, but with effort keep similarity with original version, finally was gotten adaptation version the FES – R form, which is usable for research in future.